Associations among Self-Reported Mental Health, Physical Activity, and Diet during the COVID-19 Pandemic. Issue 4 (December 2022) - Andersen, Jennifer A.; Rowland, Brett; Gloster, Erin; Willis, Don E.; Hernandez, Nestor; Felix, Holly C.; Long, Christopher R.; McElfish, Pearl A.
Background: Understanding the relationship between physical activity, diet, and mental health during the COVID-19 pandemic may help inform resources encouraging healthy lifestyle choices during the time of an increased threat to health and wellbeing.Aim: Our objective was to examine how self-rated mental health was associated with engagement in physical activity and consumption of fruits and vegetables during the COVID-19 pandemic.Methods: The study utilized cross-sectional survey data from adults (≥18 years of age) living, working, and/or receiving healthcare in Arkansas (n = 754). Multivariable regression models were used to examine the associations between self-rated mental health and the number of days respondents engaged in 30 min of physical activity and the number of days respondents consumed five or more servings of fruits and vegetables.Results: Respondents who reported somewhat poor/poor mental health reported engaging in at least 30 min of physical activity fewer days per week (β = -.77, p = .018) compared with those reporting excellent mental health, after controlling for sociodemographic factors and self-rated health. The significant association observed in the first two models between mental health and number of days consuming five or more servings of fruits and vegetables became non-significant after inclusion of self-rated health.Conclusion: The relationship between mental health and physical activity and diet reaffirms a need for healthcare providers to promote the importance of maintaining both a healthy physical activity level and a nutrient-rich diet in the face of challenging circumstances, such as a global pandemic.